Traditional Medicine Use Among HIV Positive Patients in Markurdi, Benue State of Nigeria - Akunne, Maureen; Emerenini, Chinenye; Anetoh, Maureen; Okonta, Eleje (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Traditional medicine (TM) is a collection of skills, knowledge, and practices based on theories, beliefs, and experiences from various cultures that are used to maintain health as well as to prevent, diagnose, improve, or treat physical and mental disorders. There exist a number of non-conventional medicines practices in the world today. Limited documented data exist that addressed the use of traditional medicines among HIV patients in Nigeria. Objectives: To assess the use and the pattern of use of traditional medicines among HIV positive patients. Methods: This study was a cross sectional, descriptive study carried out at the Federal Medical Center Makurdi, Benue State, middle belt, Nigeria for a period of three months. Results: In this study, nearly two-thirds (61.7%) of the participants reported that they had never used Traditional Medicine (TM) along with HIV/AIDS drugs and 16.1% reported that they began TM use after the initiation of ART. The leading forms of TM used by the patients were spiritual therapy (21.9%) and herbal therapy (16.6%). The study showed that most patients use TM without any motivating factor (62.3%) but some had motivating reasons such as religious practices (14.2%) and to deal with ART side effects (14.5%). Conclusions: The use of TM among HIV/AIDS patients on antiretroviral therapy (ART) was unusual. Spiritual and herbal therapies were the most commonly employed TMs among the participants in the study. Although a small percentage of patients reported deteriorated disease condition as a result of using TM with ART, a handful of users reported improvement after treatment.